Analisis Strategi Pemasaran Untuk Meningkatkan Daya Saing Pada Cafe Senja Coffee - Agum Murtaib; Ersha Wiriani Safitri; Putri Dasti S Harahap; Sarifah Aini; Yolanda Citra; Dian Puji Puspita Sari (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
The purpose of this research is to examine the marketing tactics used by Cafe Senja Coffee to increase its competitiveness compared to other cafes. This research uses a qualitative descriptive methodology, collecting data through observation, documentation and interviews. The findings of this study show how good Cafe Senja Coffee's marketing approach is in promoting its products and improving their quality. To maintain business growth and competitiveness, Cafe Senja Coffee continues to strive to improve its marketing plan.